Characterization of the Properties of the Biocomposite Material 15 mass% HA/PLA. Issue 1 (21st August 2022) - Mihoc, Alexandru Bejinaru; Repanovici, Angela; Druga, Corneliu; Serban, Ionel; Mitu, Leonard; Rosca, Ileana
Abstract: The objective of this study is to investigate the mechanical properties and visco‐elastic coefficients of the biocomposite material 15 mass% HA/PLA. The biocomposite material is manufactured using known technology: extrusion‐composition followed by injection molding. The general mechanical properties are evaluated experimentally using standard tensile and bending tests using five specimens made according to ASTM standards. The vasco‐elastic behavior is investigated using the DMA AR‐G2 Rheometer. The paper also investigates the microstructure of the mechanically stressed specimen breaking surface. Following the experimental research, a database is obtained in numerical form, diagrams, and fractographic images. The paper presents conclusions regarding the mechanical and dynamic behavior of the biocomposite material 15 mass% HA/PLA. The general results of the study provide practical guidance on the usefulness of biocomposite material 15 mass% HA/PLA for orthopedic biomedical applications.